Hierarchical lath colonies induced by dislocation rearrangement improve thermal cyclic stability of NiTi shape memory alloy. (1st July 2023) - Xu, Kengfeng; Luo, Jiao; Yang, Zhongsheng; Li, Miaoquan
Abstract: High thermal cyclic stability is achieved in Ti-50.8at.%Ni alloy by fabricating hierarchical lath colonies along 112 B 2 planes using isothermal compression and aging. Transformation temperature shift between the 1st and 20th thermal cycle is 0.03∼0.27°C, which results from boundary strengthening of hierarchical lath colonies. Hierarchical lath colonies are controlled by dislocations. Compression induces b = 1 2 [ 1 ¯ 11 ] screw dislocations on [ 1 ¯ 11 ] ( 12 1 ¯ ) slip system with anti-phase boundaries (APBs) located on ( 12 1 ¯ ) B 2 plane, while aging promotes dislocation motion and rearrangement, and adjustment of atomic site occupation in local structure near APBs. When distance of APBs is large, one-direction lath-colony boundaries and one-direction lath colony form. When distance of APBs reduces, clover-shaped lath-colony boundaries form, and hierarchical lath colonies are recognized. If area of APB reduces, lath-colony boundaries and lath colony vanish. These findings show the potential for improving properties of NiTi alloy by dislocation engineering. Graphical abstract: Image, graphical abstract